Evaluation of a transverse perineal approach to the canine vagina and vestibule - Sarah E. Saylor; Kyle G. Mathews (Frontiers in Veterinary Science)
There are a variety of surgical conditions impacting the canine vagina and vestibule that require access through a caudal approach. A standard vertical episiotomy involves making an incision beginning ventral to the anus and extending ventrally through the dorsal commissure of the vulva and into the lumen of the vestibule and distal vagina. The objective of this study was to determine if complex vaginal procedures could be performed via a transverse perineal approach, thus eliminating the need to incise and reconstruct the vulva as performed in a standard episiotomy, and to evaluate the feasibility of vaginal resection with vulvar-sparing vestibular urethrostomy using this transverse approach. Ten canine, female cadavers were obtained and randomly split into two equally sized groups. Cadavers in Group A (n = 5) had a vaginal resection-anastomosis cranial to the urethral papilla. Cadavers in Group B (n = 5) had a complete vaginectomy and vulvar sparing vestibular urethrostomy. Procedures for both groups were approached through a transverse perineal incision. Postoperatively, cadavers of both groups had right lateral pelvic radiographs taken with a calibration marker in the field. The distance between the location of the anastomosis (Group A) or vaginectomy site (Group B) and the skin incision was measured. The procedures in both Group A and Group B were successfully performed through a transverse perineal approach in all 10 cadavers. The mean transverse perineal incision length was 2.88 cm ± 0.49 cm, compared to a mean standard episiotomy length of 5.83 cm ± 0.79 cm. The mean distance between the location of the anastomosis (Group A) or vaginectomy site (Group B) and the skin incision measured on pre-contrast right lateral pelvic radiographs was 2.54 cm ± 0.34 cm. The results of this study confirm the feasibility of performing complex vaginal procedures through a transverse perineal approach. The described approach is shorter than the standard episiotomy, which may result in diminished discomfort and decreased surgical/anesthetic time. This approach also eliminates the need to reconstruct the vulva. Further evaluation in clinical patients is warranted.